TINJAUAN HUKUM ISLAM TERHADAP PEREMPUAN MELAHIRKAN PADA DOKTER KANDUNGAN LAKI-LAKI - Zulhamdi Zulhamdi (Al-Qadha : Jurnal Hukum Islam dan Perundang-Undangan, 2017)
In the examination of the patient, the doctor would see the nakedness of the patient to be examined and not only see the nakedness of the patientbut also touch and feel him. Whereas in Islam that same-sex genitaliathere are limits that should be seen and touched, especially the oppositesex. This study aims to determine the views of Islamic law againstpregnant women who had treatment and gave birth to the maleobstetrician. Which at the fact that pregnant women patients either anultrasound or bore little handled by a male doctor. and even most of thepregnant women are more dominant treatment in gynecologist mencompared with a specialist female, This happens mainly because theprofession obstetrician is dominated by men and also because manymothers assume that specialists content of more competent men(because physically stronger males), clever and more objective. It iscertain pregnant women who had treatment and gave birth to the maleobstetrician will reveal his private parts, genitalia fact is something thatwe must cover both men and women in order to maintain the honor inthe eyes of the beholder. So close the genitals was advocated by thereligious exception in certain circumstances and conditions whichallowed open genitalia.